A case study for exploring the alkali-aggregate reactivity of Cyprus aggregates. (June 2022) - Zahedi, Andisheh; Akpinar, Pinar
Abstract: Concrete is the most commonly used construction material in Cyprus Island as it is all around the world. Even though thousands of tons of concrete are manufactured in both North and South Cyprus, the alkali-aggregate reactivity (AAR) of the crushed (quarried) aggregates has not been previously investigated in a systematic way. The lack of information on the AAR likelihood of Cyprus aggregates in the related literature has caused a lack of awareness about this durability problem in the island and hence, sufficient controls for taking necessary levels of precautions could not be made over the past decades. Two aggregate samples from North Cyprus and another type of aggregates from South Cyprus were obtained from active quarries and tested within this case study for the first time with RILEM tests in order to verify the likelihood of both alkali-silica and alkali-carbonate reactivities of Cyprus Aggregates. The results obtained from RILEM tests and the supplementary SEM analysis showed that both the North (limestone) and South (diabase) Cyprus aggregates exhibit significant levels of alkali-silica reactivity when they are used with composite cement, which is commonly preferred for its advantages. Results also indicated that the mortar batch including the second type of North Cyprus aggregates (dolomitic limestone) with the mentioned cement is potentially reactive for alkali-carbonate reaction as well. The experimental information provided for the first time with this case study is critical both for further Cyprus durability research studies to be carried out and also for improving the quality of local construction activities.